2021
DOI: 10.1021/acssynbio.0c00649
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR-Mediated Strand Displacement Logic Circuits with Toehold-Free DNA

Abstract: DNA nanotechnology, and DNA computing in particular, has grown extensively over the past decade to end with a variety of functional stable structures and dynamic circuits. However, the use as designer elements of regular DNA pieces, perfectly complementary double strands, has remained elusive. Here, we report the exploitation of CRISPR-Cas systems to engineer logic circuits based on isothermal strand displacement that perform with toehold-free double-stranded DNA. We designed and implemented molecular converte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…Once the R-loop is formed, the non-targeted DNA strand that has been displaced can interact with other nucleic acids supplied in trans [20]. Previously, we showed that this mechanism is instrumental to engineer toehold-free DNA circuits for logic computation [17]. Here, the interaction of the beacon with the displaced strand causes the reconfiguration of the former separating the fluorophore from the quencher, thereby producing a fluorescent signal ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Once the R-loop is formed, the non-targeted DNA strand that has been displaced can interact with other nucleic acids supplied in trans [20]. Previously, we showed that this mechanism is instrumental to engineer toehold-free DNA circuits for logic computation [17]. Here, the interaction of the beacon with the displaced strand causes the reconfiguration of the former separating the fluorophore from the quencher, thereby producing a fluorescent signal ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, increasing developments on portable fluorescence microscopy coupled to mobile phones, already applied to detect SARS-CoV-2 [12,33], are appealing and might be used to characterize our CRISPR-Cas9 reactions. A cell-free expression system might also be interfaced to achieve a detection with a colorimetric readout [34], given that strand displacement allows nucleic acid conversion [17]. This would enable point-of-care diagnostics and field- Finally, we envision the application of computational methods to automate the sequence design of the different nucleic acid species that COLUMBO requires, given a series of energetic and structural specifications [35,36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Single-stranded DNAs used as input strands are relatively inexpensive, stable in aqueous solutions, and can be hybridized with RNA to form RNA–DNA duplexes. For instance, as presented by Lorena Parlea of the National Cancer Institute, single-stranded RNA toeholds can be used to drive the reassociation of RNA–DNA hybrids to transition from inert to functional products in cells. The same working principles can be implemented for the controlled organization of inorganic materials ( e.g. , quantum dots) that is synchronized with the activation of therapeutic responses inside diseased cells .…”
Section: On Dynamic Structures and Logic Gatingmentioning
confidence: 99%
“…DSD can be combined with other technologies and utilized in a wide range of applications. So far, DSD has been combined with CRISPR technology (Ishino et al, 1987;Montagud-Martínez et al, 2021), DNA origami (Rothemund, 2006;Zhang et al, 2022), enzymes (Bucci et al, 2022;Schaffter and Strychalski, 2022), proteins , etc. These combinations effectively expand the application scenarios for DSD.…”
mentioning
confidence: 99%